PERENCANAAN KEBUTUHAN PERLARATAN PRAKTEK PADA MATA PELAJARAN ILMU UKUR TANAH SMKN 1 SUMATERA BARAT - 999-1018 , Dedi Famina Riyo (Universitas Negeri Padang, 2016)
ABSTRACTThis research is purposed to find out the requirement of training utilities for land geometry subject at SMKN 1 west Sumatra. Research was conducted by observation and interview. Data analysis technique that used in this research was descriptive quantitative analysis. Research finding shows that there are 15 training utilities that can be applied for land geometry subject. Types and numbers of utilities to fulfill training utilities requirement are 7 gages, 5 measuring tapes, 28 measuring pens, 24 yalons, 5 data boards, 5 square prisms, 5 strands, 6 hoses, 5 measuring signs, 6 measuring vessels, 5 tripod, 5 leveling, 5 compasses, 5 theodolites, 6 umbrellas.Keywords: requirement analysis, utilities.